Social justice: The heart of medical education - Allen L. Hixon; Seiji Yamada; Paul E. Farmer; Gregory G. Maskarinec (Social Medicine Publication Group, 2013)
Building on the long-standing institution of the Hippocratic Oath, the authors suggest that all physicians- in-training must be taught the principles affirmed by the 1978 Declaration of Alma-Ata. Physicians should recognize that health is a fundamental human right and that gross inequalities in health care are unacceptable for moral, political, social, and economic reasons. Incorporating an explicit focus on social justice in medical education will lead to the training of physicians who understand that to advance the goal of "health for all" they must work toward more equitable distribution of health care and the elimination of health disparities, both within the U.S. and internationally. Learning to understand the social determinants of health, to advocate for equitable health system change, and to advance social justice throughout their careers should be the focus of this training. As this training prepares leaders to press for system change in the U.S., it also aligns with the global trend of recognizing human rights as a core competency of medical education.